Keadilan Ekologi Berbasis Hukum Kehutanan dan Lingkungan Hidup dalam Perspektif Dakwah dan Tarbiyah - Rohmy, Atikah Mardhiya; Nihayaty, Arini Indah (Institut Agama Islam Syarifuddin Lumajang, 2025)
Forests are the main contributor of oxygen for life on earth, providing around 30% of the total global oxygen requirement. Forest management based on ecological justice is an important concern for all countries in the world as an effort to maintain environmental balance and sustainability of life. Forest and environmental damage has caused a multidimensional crisis, including the climate crisis, climate change, loss of biodiversity, and environmental degradation that endanger the sustainability of life on this planet. In this context, the implementation of the Job Creation Law in the Forestry and Environmental Sector has not fully reflected ecological justice, due to political and power interventions that have given rise to conflicts of interest in forest area governance. This study uses a qualitative method with an empirical normative legal approach influenced by sociological jurisprudence. A critical approach is needed to encourage changes in forest management based on the principles of good governance, prioritizing the values ​​of ecological justice that are integrated with da'wah and tarbiyah. From a da'wah perspective, fair and sustainable forest management is a real form of amar ma'ruf nahi munkar, namely calling for goodness by protecting the environment as a mandate from Allah, while preventing damage that is prohibited in Islamic teachings. Meanwhile, from a tarbiyah perspective, good forest management reflects moral and spiritual education to build deep ecological awareness, form a society that cares about the environment and is responsible for its sustainability. The proposed strategic efforts include collaboration between da'wah movements, political parties, and state administrators to create forest management policies that are based on ecological justice and integrated with Islamic values. In addition, social movements based on tarbiyah values ​​are needed to encourage active community participation down to the grassroots level, including utilizing mass media to spread strong and sustainable ecological da'wah messages. With this approach, it is hoped that forest management will not only be oriented towards environmental sustainability, but also reflect justice, responsibility, and harmony as mandated by Islamic values.